2018
DOI: 10.3389/fphys.2018.00561
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Heart Rate Variability as a Discriminator of Internalizing Psychopathology and Negative Affect in Children With Internalizing Problems and Healthy Controls

Abstract: Background: Internalizing psychopathology and dysregulated negative affect are characterized by dysregulation in the autonomic nervous system and reduced heart rate variability (HRV) due to increases in sympathetic activity alongside reduced vagal tone. The neurovisceral system is however, a complex nonlinear system, and nonlinear indices related to psychopathology are so far less studied in children. Essential nonlinear properties of a system can be found in two main domains: the informational domain and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 97 publications
3
18
0
Order By: Relevance
“…Entropy, therefore, was useful to detect anticipated, exposure‐, and math‐related stress. This is in accordance with growing evidence supporting the importance of measuring HR entropy: SampEn was a significant predictor of internalizing psychopathology and negative affect in a study with children with internalizing problems and healthy controls (Fiskum et al, ). A previous study (Fiskum et al, ) concluded that SampEn was a potential marker of dysregulation in the underlying neurovisceral processes vital for emotion regulation.…”
Section: Discussionsupporting
confidence: 90%
“…Entropy, therefore, was useful to detect anticipated, exposure‐, and math‐related stress. This is in accordance with growing evidence supporting the importance of measuring HR entropy: SampEn was a significant predictor of internalizing psychopathology and negative affect in a study with children with internalizing problems and healthy controls (Fiskum et al, ). A previous study (Fiskum et al, ) concluded that SampEn was a potential marker of dysregulation in the underlying neurovisceral processes vital for emotion regulation.…”
Section: Discussionsupporting
confidence: 90%
“…First, ANS function was measured only at rest and not also in response to a physical and/or psychological stressor, which may provide more nuance to the analyses. Although a large body of research has examined resting levels of cardiac vagal control (e.g., Rottenberg, ), and to a lesser extent sympathetic activity (Fiskum et al, ), this study adds to the extant literature by examining a broader pattern of potential autonomic dysfunction in depression within a bivariate autonomic space. More recent research has examined autonomic flexibility in response to physical and psychological stressors (Bylsma et al, ; Daches et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The limited available studies of children suggest similar differences. In middle childhood, children rated by their parents as displaying heightened levels of temperamental negative affect and/or internalizing problems have been shown to demonstrate lower levels of resting cardiac entropy, relative to their lower internalizing peers (Fiskum et al, 2018). Comparable associations have been noted with adolescents in more ecologically valid settings.…”
Section: The Autonomic Nervous System (Ans)mentioning
confidence: 99%